System dynamics analysis of the impact of paddy and energy subsidies withdrawal on paddy sector - Baharudin, Siti 'Aisyah (2015)
Paddy is a staple food for Malaysians while paddy production has been the main economic activity for many farmers. Despite government intervention in the paddy production, low paddy productivity has been one of the main issues that affect farmer’s income. In addition, increasing world crude oil price will directly lead to an increase in domestic fuel price for paddy machine. Indirectly, it also affect the fertilizer price and paddy sector. Previous research has pointed out the rationales of subsidies withdrawal, such as; insufficient paddy production, market imperfection and profit loss from paddy sale. However, the analysis by most research did not integrate all factors and deemed as unable to provide comprehensive analysis of the problem. Moreover, the analysis did not address the issue of increasing energy prices and its effect on energy usage level in paddy production. Hence, this study focus on four main objectives; (i) to formulate the share of energy use by activity and sources in the paddy sector; (ii) to simulate a change in world crude oil price on the paddy productivity and expenditure; (iii) to simulate the impact of paddy and fuel subsidies removal on the expenditure and farmers’ income; and (iv) to simulate the impact of various policy scenarios on the paddy sector. Energy use is important in paddy production because it requires energy in all production activities, both in direct and indirect energy use. There are four main activities involved such as land preparation, planting, crop management and harvesting. The direct energy use is in the form of fuel and human labour, while the indirect energy is required in the application of fertilizers, pesticides and seed. Hence, this study is required to formulate the shares of energy use in the paddy sector using Energy Analysis (EA) methodology. Besides, this study calls for simulation of System Dynamics (SD) methodology on the (i) implication of change in world crude oil price; (ii) the impact of paddy and energy subsidies withdrawal; and iii) alternative policy to improve paddy sector. Energy analysis shows that higher energy use will increase paddy productivity. However, once the usage level reaches its maximum threshold, the productivity level will decline. Crop management activities show the highest energy use at 67%, followed by land preparation (21.7%), harvesting (10%) and planting (1.3%) activities. Fuel is the highest direct energy user,while fertilizer proves to be the highest consumer of indirect energy. Energy efficiency level for paddy production is 4.08. System dynamics model is used to identify the underlying problematic structure by modelling the land use, productivity, consumption, input, allocation input, farmer’s income, expenditure, farm cash, energy use, farm and technology practices sub-models. The simulation results have replicated the historical data, in which an increase in world crude oil price shows an increasing paddy expenditure by 3.8%. However, a 1% increase in fuel price will increase the fertilizer price by 3.4%. This shows that the actual cost of paddy production is more higher if the paddy price is not subsidised. Meanwhile, simulation result for removal of both paddy and fuel subsidies indicates a drop in paddy productivity by 10.3% compared to the decrease in income by 17.9%. The decline in productivity has inherently increased the import by 17.5%, hence reduces selfsufficiency level (SSL) by 10.3%. The main objectives of the paddy policy is to increase the SSL through increasing productivity and farmers’ income, while reducing the dependency on imported rice. With this, researcher has examined the effect of future policy scenarios which are examines the implications of the removal of paddy and fuel subsidies together with the implementation of policy scenario (PS); (i) PS1 (R&D in new paddy variety); (ii) PS2 (PS1 + R&D in organic farming); (iii) PS3 (PS1 + PS2 and improved farm practices); and (iv) PS4 (PS1 + PS2 + PS3 and adaption of technological practices). Based on the alternative policy scenarios, scenario PS4 gives the highest result compared to other policy scenarios with almost all variables increase up to 40% from the Base Run. Within the 15 years of simulation period, productivity is approximated to increase by 6.5 tonnes/ha and rice SSL is expected to increase by 79%.